Combination of SVM, LDA, PCA and linear regression under fuzzy system in human face recognition - Ahammad, Bulbul; Jude Rozario, Liton; Majumder, Anup; Imdadul Islam, Md. (International Journal of Engineering and Technology, 2019)
One of the main applications of image processing is recognition of human face. In this paper, we worked on several benchmark databases of human face to identify a person based on Linear Regression, SVM (Support Vector Machine and Viola-Jones Object detector), LDA (linear discriminant analysis) and PCA (Principal Component Analysis). All the four methods are combined under Fuzzy system and we get the accuracy of 96.4% which is higher than any individual method.